Luaran Klinis dan Komplikasi Terapi Endovaskular pada Pasien Stroke Iskemik Akut dengan Trombolisis Intra-Arteri dan Trombektomi Mekanik pada Setting Penanganan Kritis - Retnaningsih, Retnaningsih; Tugasworo, Dodik; Kurnianto, Aditya; Tri Rahayu, Fitriani (PERDOSNI, 2025)
Introduction: Acute ischemic stroke (AIS) is a major cause of disability and death worldwide. Mechanical thrombectomy (MT) has become the standard endovascular therapy for AIS with large vessel occlusion, though incomplete reperfusion remains a concern. Intra-arterial thrombolysis (IA-T) has emerged as a potential adjunct therapy to enhance reperfusion. Aim: To evaluate clinical outcomes and complication rates between IA-T plus MT compared to MT alone in AIS patients treated in the ICU of Dr. Kariadi Hospital, Semarang. Methods: A total of 38 AIS patients with MCA occlusion who received endovascular reperfusion therapy were divided into two intervention groups: IA-T + TM (n=18) and TM alone (n=20). Outcomes according to Modified Rankin Scale (mRS) score and complication data were compared between groups. Results: Patients in both groups had similar baseline characteristics. A higher percentage of patients in the IA-T + MT group achieved favorable mRS scores (0–2) compared to the MT-only group (72.2% vs 65%), though the difference was not statistically significant (p=0.632). No significant differences in complication rates were found. Discussion: The combination of IA-T and MT showed a trend toward better functional outcomes without significantly increasing complications. This suggests potential benefit in selected cases. Keywords: ischemic stroke, intra-arterial thrombolysis, mechanical thrombectomy